Remote results of treatment of patients with advanced ovarian cancer after interval and delayed cytoreductive surgery: a retrospective single-center study - P. I. Sorokin; D. O. Utkin; M. V. Novozhilov; Z. T. Abduragimova; S. E. Kulikova (Опухоли женской репродуктивной системы)
Background. Neoadjuvant chemotherapy is an option for the treatment of advanced ovarian cancer. The data about optimal chemotherapy cycles before surgery is contradictory. We conducted a retrospective study to evaluate long-term outcomes following interval and delayed cytoreductive surgeries.Aim. To compare long-term outcomes following interval and delayed cytoreductive surgeries.Materials and methods. The study included 115 patients who suffered from advanced ovarian cancer (IIIC–IVB stages) and were operated in Moscow City Oncology Hospital No. 62 after 3–4 (interval cytoreductive surgery; n = 58) or 5–6 cycles (delayed cytoreductive surgery; n = 57) of neoadjuvant chemotherapy between January 2018 and December 2021. The primary endpoint is overall survival; secondary endpoint is disease-free survival.Results. Median disease-free survival was 18 months in the interval cytoreductive surgery group and 16 months in the delayed cytoreductive surgery group (p >0.05). Median overall survival was 47 months in both groups (p >0.05).Conclusion. The number of cycles of neoadjuvant chemotherapy did not affect overall and disease-free survival in patients with advanced ovarian cancer.